Artysta — neurobiolog? Malarskie manipulacje procesami widzenia - Łynnik, Maria (Z Teorii i Praktyki Dydaktycznej Języka Polskiego, 2020)
Art and the notion of beauty related thereto are both disciplines and states which are quite unobvious and thereby requiring us to ask the question: Why is it that human beings have in their minds an inherent need to witness the beauty along with — resultant — need to create and receive art? The author of the text — by devising some neurobiological tools — attempts to elicit relative laws of beauty reception, and simultaneously she utilises the instruments of neuroaesthetics, which is a field of science that investigates the impact of art on processes taking place in the human brain. She explores, among other things, mechanisms put to use, consciously or otherwise, by artists in order to make their works a peculiar stimulus. The author describes a series of “tricks” used by visual arts creators who model the particular ways the visual perception processes function.